Biological dynamics of hepatitis C virus infection in haemodialysis patients in Pahang Darul Makmur - Abdul-M., Mohammad Saad (Kulliyyah of Medicine, International Islamic University Malaysia, 2010)
Hepatitis C virus (HCV) is a member of the family Flaviviridae (Flamm, S. L., 2003). HCV has 6 major genotypes. HCV is a global disease which has been described by WHO as a “viral time bomb”. It is estimated that about 170 million people, 3% of the world's population are infected by HCV. HCV is frequent in patients undergoing chronic haemodialysis (HD) (Fabrizi, F. et al., 1998), with prevalence between 8-10%. In Malaysia, the sero-prevalence of HCV is 1.6% (Theodore, Sy and Jamal, M. Mazen, 2006), sero-prevalence rates, range from 3% in blood donors to 85% in intravenous drug users (Sinniah, M. and Ooi, B.G. 1993). Measuring HCV viral load and identifying HCV genotype became standard procedures before starting anti-HCV therapy in France (Lefrère, Jean-Jacques et al., 2005) and other countries. The purpose of measuring viral load is to follow up the response to anti-HCV therapy (Yoon, Joonho et al., 2007; Halfon, Philippe et al., 2006) and to follow up the natural course of the virus infection (Fabrizio, Fabrizi et al., 2000). The aim of this study is to elucidate the biological dynamics of HCV infection in patients with end stage renal disease undergoing maintenance haemodialysis, the effect of HD on alpha-interferon levels, the possible role of alpha-interferon on viral load, the difference in viral loads between the different genotypes and the effect of viral load on liver damage.In this study 27 genotyped HCV infected patients were recruited from haemodialysis clinics in Pahang. HCV infection in these patients has been screened by Enzyme-Linked Immunosorbent Assay and confirmed by RT-PCR. Patients' serum samples were taken before and after haemodialysis sessions three times, one month apart over a period of 3 months. The HCV viral load, plasma alpha-interferon levels and liver function tests were the specific tests performed. The viral load results will be compared with the patients' functional status of the liver and with the different HCV genotypes. The study showed that the viral load varied significantly over the three months period of the study. The differences between pre and post-haemodialysis viral load were measured and found to be statistically insignificant. Also no correlation could be demonstrated between viral load and liver function tests results. Moreover, no correlation could be found pre-haemodialysis plasma interferon-α levels and prehaemodialysis viral load. The differences between pre and post-HD plasma interferon- α levels was measured and found to be statistically insignificant. However HCV genotype 1 viral load was significantly higher than genotype 3 viral load. Patients undergoing maintenance HD seems to experience a milder course of HCV infection. It can be concluded from the results obtained in this study that the HCV viral load in HD patients, although low, significantly fluctuates with time, hence it is probably crucial to take more than one measurement for the viral load when assessing and following up the virological status of these patients, especially when planning for antiviral therapy. Moreover, the study showed that the one-step reverse-transcriptase real-time PCR assay has the potential for rapid HCV genotyping at the same time as measuring the viral RNA load. Genotype 1 was associated with a higher viral load as compared to genotype 3. This might be one of the reasons for the greater difficulty faced in eradicating genotype 1 with anti-HCV therapy and its associated unfavourable prognosis. The biochemical evidence of liver injury did not correlate with the viral load supporting the notion that liver injury in HCV infections is immune-mediated.